PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Yolanda Fransiska Lombu’u Sinaga; Benjamin Albert Simamora; Injen Pardamean Butarbutar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out how much influence financial literacy and lifestyle have on the financial management of Economic Education Study Program students at HKBP Nommensen Pematangsiantar University.This research is of quantitative type. The sampling technique used simple random sampling with 75 respondents. Collection technique using a questionnaire. Instrument testing uses normality tests and reliability tests. The data analysis technique uses classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing, namely multiple linear regression analysis, t-test, f-test, and coefficient of determination.Data from research results and partial test data management (t-test) show that the variable The variable Management of simultaneous test data (f-test) shows that F count is 17.772 > F table is 3.12, so it can be concluded that financial literacy and lifestyle have a positive and significant effect on student financial management.